Political uncertainty cycles and the impact of oil shocks on supply chain pressures - Corey Williams (Economies, 2025)
This study explores how energy price inflation affects supply chain pressures under different levels of political uncertainty. Using local projection impulse-response functions, we examine the effects of oil price shocks under two regimes: one with above-average levels of political uncertainty and another with below-average uncertainty. While previous research has focused on the direct macroeconomic impacts of oil price shocks, particularly on firm costs and consumer prices, this study highlights the effects of these shocks on supply chain disruption as a whole. Our findings indicate that heightened political uncertainty significantly amplifies the impact of oil price shocks on supply chain pressures, causing notable and persistent disruptions. Conversely, when political stability is high, the response of supply chains to the same shocks is minimal, suggesting that a stable political environment fosters greater resilience in supply chains.
Keywords: E32; Q43; Q48; 330; oil shocks; political uncertainty; supply chain disruptions